QOL-58. IMPROVEMENT IN VISUAL ACUITY OF PEDIATRIC PATIENTS WITH BRAIN TUMORS WITH BEVACIZUMAB. Issue 2 (22nd June 2018) - McEvoy, Matthew; Hemenway, Molly; Raybin, Jennifer; Green, Adam; Nellan, Anandani; Levy, Jean Mulcahy; Vibhakar, Rajeev; Foreman, Nicholas; McCourt, Emily; Dorris, Kathleen
Abstract: BACKGROUND: Bevacizumab, a monoclonal antibody that targets vascular endothelial growth factor, has been shown in a small series of children with vision loss associated with optic pathway gliomas (OPG) to produce marked vision recovery. METHODS: A single-institution retrospective record review of pediatric patients who had poor visual acuity and received bevacizumab from 2014-2017 was performed at Children's Hospital Colorado. Data collected included demographics, pathology information, visual acuity exams (Snellen), visual field exams, optical coherence tomography (OCT), and bevacizumab dosing and toxicity. RESULTS: Eighteen patients (10:8, male:female) received bevacizumab for poor visual acuity. The median age of patients at the start of bevacizumab treatment was 5.2 years (range, 1.3-21.5 years). Thirteen patients had OPGs, three patients had craniopharyngioma, and two had other brain tumors with vision loss due to hydrocephalus at diagnosis. Median time from tumor diagnosis to start of bevacizumab was 0.6 years (range, 0.1-12.9 years). Most (11/18) patients (8 OPG, 2 craniopharyngioma, 1 glioneuronal tumor) experienced improvement (i.e., LogMAR decrease >0.1) in visual acuity in at least one eye. Bevacizumab (median of 13 doses and range of 4-20 doses administered per patient) was tolerated well overall. Seven patients experienced transient toxicities (including proteinuria, hypertension, and headaches). OCT analysis is ongoing. CONCLUSIONS: Bevacizumab appears to improve visual acuity in some children with vision loss associated with injury to the optic apparatus from tumor or hydrocephalus. A clinical trial to investigate the use of bevacizumab for vision recovery in pediatric brain tumor patients is warranted.